Workload and health professional nursing: integrative review - Willkslainy Lima Paixão, Márcia Teles de Oliveira Gouveia, Maria Lúcia do Carmo Cruz Robazzi, Cynthia Roberta Dias Torres, Fernanda Valéria Silva Dantas Avelino (Revista de Enfermagem da UFPI)
DOI: https://doi.org/10.26694/reufpi.v2i3.940